2012
DOI: 10.1007/s11033-012-2333-1
|View full text |Cite
|
Sign up to set email alerts
|

Congenital lamellar ichthyosis in Tunisia is caused by a founder nonsense mutation in the TGM1 gene

Abstract: Lamellar ichthyosis (LI, MIM# 242300) is a severe autosomal recessive genodermatosis present at birth in the form of collodion membrane covering the neonate. Mutations in the TGM1 gene encoding transglutaminase-1 are a major cause of LI. In this study molecular analysis of two LI Tunisian patients revealed a common nonsense c.788G>A mutation in TGM1 gene. The identification of a cluster of LI pedigrees carrying the c.788G>A mutation in a specific area raises the question of the origin of this mutation from a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…Hence, children with ichthyosis may require lifelong prophylaxis of calcium and vitamin D . In our patient, a nonsense mutation, the c.788G>A, p.W263X in the TGM1 gene was identified, which is a founder nonsense mutation . The latter was reported in association with lamellar ichthyosis, erythrodermic congenital ichthyosis, and even bathing suit ichthyosis.…”
mentioning
confidence: 70%
“…Hence, children with ichthyosis may require lifelong prophylaxis of calcium and vitamin D . In our patient, a nonsense mutation, the c.788G>A, p.W263X in the TGM1 gene was identified, which is a founder nonsense mutation . The latter was reported in association with lamellar ichthyosis, erythrodermic congenital ichthyosis, and even bathing suit ichthyosis.…”
mentioning
confidence: 70%
“…Some researchers have recently confirmed that five different TGM1 mutations are common in some specific ethnic populations. These studies used haplotype‐based analysis with polymorphic microsatellite markers: c.1223_1227delACACA in Portuguese and Galician (NW Spain) patients, c.2278C>T and c.984+1G>A in Galician patients, c.788G>A in Tunisian patients, and c.877‐and 2A>G in Italian, North American and Norwegian patients . This evidently low genetic heterogeneity raises the possibility of founder effects.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Lamellar ichthyosis is a rare, autosomal recessive skin disorder characterized by generalized hyperkeratosis, with estimated incidence rates of 1:250000. [1] Lamellar ichthyosis is a rare, autosomal recessive skin disorder characterized by generalized hyperkeratosis, with estimated incidence rates of 1:250000.…”
mentioning
confidence: 99%
“…[1] The primary pathogenic event seems to be follicular occlusion in apocrine gland-bearing skin. [1] The primary pathogenic event seems to be follicular occlusion in apocrine gland-bearing skin.…”
mentioning
confidence: 99%
See 1 more Smart Citation